2015
DOI: 10.1186/s12889-015-2524-5
|View full text |Cite
|
Sign up to set email alerts
|

Can housing improvements cure or prevent the onset of health conditions over time in deprived areas?

Abstract: BackgroundThere is a need for more evidence linking particular housing improvements to changes in specific health conditions. Research often looks at generic works over short periods.MethodsWe use a longitudinal sample (n = 1933) with a survey interval of 2–5 years. Multivariate logistic regression is used to calculate the odds ratios of developing or recovering from six health conditions according to receipt of four types of housing improvements.ResultsReceipt of fabric works was associated with higher likeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 33 publications
2
31
0
1
Order By: Relevance
“… 27 An analysis of the pathway between housing improvements and health conditions in Glasgow, Scotland concluded that although energy efficiency measures could help manage symptoms, they did not prevent the occurrence of disease. 28 In addition, another study cautioned that evaluation of energy efficiency measures provided only a snapshot of historical exposure and that improvements could not mitigate health impacts of cold and damp related exposures built up over a lifetime. 8 However, as hospital admission rates increased with increasing levels of deprivation leading to greater absolute reductions in hospital admissions in the highest deprivation fifths, targeting more deprived communities could still provide an overall greater impact on health than untargeted interventions.…”
Section: Discussionmentioning
confidence: 99%
“… 27 An analysis of the pathway between housing improvements and health conditions in Glasgow, Scotland concluded that although energy efficiency measures could help manage symptoms, they did not prevent the occurrence of disease. 28 In addition, another study cautioned that evaluation of energy efficiency measures provided only a snapshot of historical exposure and that improvements could not mitigate health impacts of cold and damp related exposures built up over a lifetime. 8 However, as hospital admission rates increased with increasing levels of deprivation leading to greater absolute reductions in hospital admissions in the highest deprivation fifths, targeting more deprived communities could still provide an overall greater impact on health than untargeted interventions.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that there was insufficient opportunity to alter established behaviour and ill health to result in significant reductions in health events, despite the potentially long follow-up periods during this decade-long intervention evaluation. 10 Equally, despite a lack of statistical significance, it is possible there was a practical effect. The people with pre-existing respiratory conditions and CMDs may have experienced an effect on their health service utilisation, compared with the reference group, that would have been significant had the sample size been larger.…”
Section: Discussionmentioning
confidence: 99%
“…9 A simplified version of this logic model was tailored to the GoWell programme. 10 We have adapted the housing improvements to health pathways for the CHS intervention ( Table 1).…”
Section: Logic Model Of Housing Improvementsmentioning
confidence: 99%
“…Evidence on the subject can be found for a wide range of settings [67] and populations [5; 8]. The UK has been a major focus for research in this area [1].…”
Section: Introductionmentioning
confidence: 99%